Comparative efficacy of raw and HNO3-modified biochar derived from rice straw on vanadium transformation and its uptake by rice (Oryza sativa L.): Insights from photosynthesis, antioxidative response, and gene-expression profile. (15th November 2021) - Mehmood, Sajid; Ahmed, Waqas; Rizwan, Muhammad; Imtiaz, Muhammad; Mohamed Ali Elnahal, Ahmed Said; Ditta, Allah; Irshad, Sana; Ikram, Muhammad; Li, Weidong
Abstract: Low concentrations of vanadium (V) are essential for various plant species but it becomes toxic to plants, animals, and humans at high levels. A significant amount of V is currently being emitted into the atmosphere due to intensified industrial processing. Therefore, this study aimed at evaluating the effect of raw (BC) and HNO3 -modified biochar (OBC) derived from rice straw on growth, photosynthetic assimilation, relative chlorophyll content, SPAD index, ion leakage, enzyme activities, hydrogen peroxide (H2 O2 ), bioavailability and V uptake by rice in a laboratory-scale experiment. Characterization of OBC and BC by FTIR (Fourier transform infrared spectroscopy), SEM (scan electron microscopy), BET (Brunauer–Emmett–Teller), elemental analysis, and z-potential revealed a substantial difference between both of them. The V-stress significantly reduced the rice plant growth, biomass yield, chlorophyll parameters, root length and surface area. Under V-stress conditions, root accumulated more V than shoots and OBC significantly improved the above-mentioned parameters, while, decreasing hydrogen peroxide (H2 O2 ) and malondialdehyde (MDA) levels in plants. The antioxidant function and gene expression levels induced by V-stress and OBC application further increased the expression profile of three genes ( SOD, POD, and CAT ) encoding antioxidant enzymes and one metal-tolerant conferring gene ( OsFSD1 ). In summary, these results demonstrated the critical role of OBC in mitigating the detrimental effects of high V-stress on rice growth and enhancing plant defence against V-stress. Graphical abstract: Image 1 Highlights: High V concentration cause drastic effects on plant growth, generate oxidative stress. Rice growth was increased with the increase in C and N contents due to modified biochar. Oxidized biochar boosted the expression of metal tolerant genes. Oxidized biochar illustrates the use of eco-friendly and cost-effective approach to remediate V.